Faktor-Faktor yang Mempengaruhi Kualitas Laba pada Industri Pariwisata di Indonesia - Elsa Amalia Dita; Febri Rahmi (Yayasan Almanar Pujud, 2026)
The purpose of this study is to examine factors that affect the quality of profits, including Operating Cash Flow, Capital Structure, Investment Opportunity Set, Liquidity, and Company Size in service companies in the Indonesian Tourism Industry sub-sector service companies listed on the Indonesia Stock Exchange for the 2022-2024 period. This study uses secondary data obtained from the official IDX website for the 2022–2024 period. The sample consists of 18 companies selected using a purposive sampling technique. Data analysis was conducted using panel data regression analysis with EViews. The results indicate that Operating Cash Flow, Investment Opportunity Set, and Firm Size have a significant effect on Earnings Quality. Meanwhile, Capital Structure and Liquidity do not have a significant effect on Earnings Quality. The variables of operating cash flow, capital structure, investment opportunity set, liquidity and company size can contribute 74.78% to profit quality, while 25.22% is influenced by other factors not examined in this study.